ALGEBLOCKS AS A PLAYFUL-TEACHING TOOL FOR LEARNING BASIC OPERATIONS WITH WHOLE NUMBERS - Vega , Luis Darío Castillo; Medina, Alcibíades; Galástica, Narciso (Seven Editora, 2025)
The world of algebra is very complex, and the use of tools and techniques that facilitate its understanding are key elements in the teaching-learning process. This educational project seeks to improve the teaching of integer addition and subtraction operations to pre-school students through the use of Algeblocks. Training is provided to future mathematics teachers, who value the experience of using Algeblocks as a fun tool for more meaningful learning. DOI: https://doi.org/10.56238/sevened2025.021-070